Complex Assessment of Quality Indicators of Fabrics Obtained from a Mixture of Fiber and Secondary Material Resources of Different Composition - Patkhullayev Sarvarjon Ubaydulla ogli; Ochilov Tulkin Ashurovich; Yodgorova Hilola Isroilovna; Shumkarova Shamsiya Pulatovna; Yuldasheva Mavluda Turamuradovna (International Journal on Orange Technologies, 2023)
in this article, 66.4% cotton fiber with 27.0% viscose fiber+6.6% nitron fiber secondary material resources for hemp yarn, 66.4% cotton fiber with 27.0% lavsan fiber+6.6% nitron fiber secondary material resources, 66.4% cotton fiber with 27.0% nitron fiber+6.6% cotton fiber secondary material resources, 66.4% cotton fiber with 27.0% lavsan fiber+6.6% viscose fiber secondary material resources . 100% cotton yarn was used to produce sari weaves and their quality indicators were comprehensively evaluated.